Vascular Invasion without Lymphatic Dissemination is an Independent Predictive Indicator of Relapse and Remote Metastasis in Colorectal Malignancy - Waheeb Al-Kubati (World Journal of Colorectal Surgery)
Background: Lymphovascular invasion (LVI) is a well-established predictor of recurrence and metastasis in colorectal malignancy. However, the independent effect of vascular invasion (VI) alone, without lymphatic involvement, remains unclear. Additionally, the phenomenon of stage migration, where undetected nodal or systemic involvement alters prognosis, has not been systematically considered in prior analyses. Objectives: This study investigates the prognostic role of VI in colorectal cancer (CRC) while accounting for stage migration to analyze the association of VI with recurrence and distant metastasis compared to cases with both VI and lymphatic invasion (VI+LI). Design: A retrospective cohort study. Settings: The study was conducted at a tertiary care center. Patient and Methods: We retrospectively reviewed 60 consecutive CRC patients who underwent curative resection between 2018 and 2024. The patients were categorized into VI-alone (n = 24, 40%) and VI+LI (n = 36, 60%). Stage migration was analyzed by tracking disease progression over time to assess its effect on survival trends. Main Outcome Measure: The primary outcomes included recurrence rates and distant metastasis, and the survival analysis was adjusted for stage migration to ensure that the prognosis assessment was accurate. Sample Size: The sample comprised 60 patients, of whom 24 presented VI without lymphatic dissemination and 39 presented both VI and LI. (Sixty patients; VI alone: 24, VI+LI: 36). Results: After adjusting for stage migration, the VI-alone patients exhibited a higher recurrence rate (50%) than that of the VI+LI patients (25%, P < .001). The occurrence of distant metastasis was significantly higher in the VI-alone patients (25%) compared to that in the VI+LI patients (2.8%, P < .001). The Kaplan–Meier survival analysis initially suggested better recurrence-free survival (RFS) in the VI+LI Stage I-II patients (75%) than in the VI-alone patients (45.8%, P < .05). However, after adjusting for stage migration, this difference artificially inflated because delayed lymph node detection shifted patients from Stage I-II to Stage III. Logistic regression highlighted VI-alone as an independent predictor of recurrence (Odds ratio (OR) 174 = 0.26, 95% Confidence Interval (CI): 0.06–0.87, P = .027) and metastasis (OR = 0.12, 95% CI: 0.01–0.90, P = 175.013). Conclusion: VI is a critical independent predictor of recurrence and metastasis in CRC, even without lymphatic involvement. Stage migration significantly influenced the survival trends, explaining the paradoxical improvement in early-stage VI+LI patients. These findings emphasize the need for closer monitoring and refined staging approaches to prevent the underestimation of recurrence risk in patients with VI. Limitations: This study is limited by its retrospective design, single-center setting, and relatively small sample size. Larger prospective multicenter studies are needed to validate these findings. Conflict of Interest: None.